An overview of family management in the care of children with cancer - Nadya, Ahsana; Asniar, Asniar; Febriana, Dara (KHD-Production, 2025)
Effective family management can enhance a family's ability to cope with illness, maintain psychological stability, and support treatment outcomes. However, this has not yet been explored explicitly among families caring for children with cancer in the Province of Aceh. This study aims to analyze the characteristics of family management in caring for children with cancer, to provide a basis for designing appropriate nursing interventions to enhance family caregiving practices. This quantitative study employed a cross-sectional design, involving a total sample of 62 mothers and 30 fathers. Participants were families of children with cancer residing in various cities across Aceh Province who were receiving treatment in Banda Aceh. Data collection took place from March to April 2025. A non-probability, purposive sampling technique was employed, and quantitative data were collected using the Family Management Measure (FaMM). The results indicated that fathers reported higher scores compared to mothers across nearly all subscales of family management, including Child’s Daily Life (3.867), Condition Management Ability (3.455), Condition Management Effort (3.483), Family Life Difficulty (3.576), and View of Condition Impact (4.017). In contrast, mothers demonstrated slightly higher scores on the Parental Mutuality subscale (3.772). The results suggest that fathers tend to have a more positive perception than mothers regarding most dimensions of family management, including the child’s daily life, the ability and effort to manage the condition, and the perceived impact of the illness on family life. However, mothers showed a slightly higher perception of parental collaboration.